Peran Pelayanan Kesehatan Sekolah dalam Meningkatkan Status Kesehatan Remaja di Indonesia - Gazali, Muhammad; Zaroni, Muhammad (Journal of Applied Health Sciences, 2026)
School health services play a strategic role in supporting the improvement of adolescent health status, particularly in developing countries such as Indonesia. Adolescents are a vulnerable population facing various physical, mental, and behavioral health challenges, making early promotive and preventive health interventions essential. Schools, as institutions that engage adolescents continuously, provide an effective setting for the implementation of school-based health services. This study aims to analyze the role of school health services in improving adolescent health status in Indonesia. This study employs a qualitative approach using a library research design. Data were collected from reputable national and international scientific journal articles, reports from international organizations, and relevant policy documents related to school health services and adolescent health. The data were analyzed using thematic analysis to identify key patterns, findings, and policy implications emerging from the literature. The findings indicate that school health services, particularly through the School Health Unit (UKS) program, contribute positively to improving adolescents’ health knowledge and health literacy, promoting healthy behaviors, and supporting both physical and mental health outcomes. However, the implementation of school health services in Indonesia still faces several challenges, including limited resources, regional disparities, and weak cross-sectoral coordination. In conclusion, strengthening school health services through integrated policies, capacity building for implementers, and active involvement of all stakeholders is crucial to achieving sustainable improvements in adolescent health status in Indonesia.